Supporting the economy through public expenditures - Ciobanu, Ramona (Transilvania University Press, 2010)
The exertion state functions internally and externally is made through a complex system of institutions and bodies. In order to support them, the state spends each year important amounts of money. Directly or indirectly, all public expenditures have effects on the economy, but in supporting it, the most relevant expenditures are on economic actions, education, culture, and health as well as on research and development.
Keywords: public expenditures; economic growth; education; culture; innovation